Cattari Ariya Saccani: The Essence of Buddhism Teaching in Management Control Systems - Irma Cahyani Kawi; Wiyono Pontjoharyo (Budapest International Research and Critics University, 2023)
An organization or business entity has several goals including providing happiness to stakeholders, creating harmony with the surrounding environment and nature, and instilling ethical values that are universal-transcendental to each member. One of the important role holders in an organization or business entity is human resources, so that self-control of each individual is an important thing that needs attention. According to several studies that have been conducted, business entities or organizations that involve spiritual aspects in their activities have proven to be able to survive and thrive. Management Control Systems can contribute to creating this. The three dimensions contained in humans that are relevant to SPM that are important to control are, spirit, soul, and mind. Cattari Ariya Saccani is one of the teachings of Buddhism which contains self-control wrapped in its noble spiritual values and holds various dimensions of control that are different from MSS in general so that it is suitable for deeper digging into the unique essence of SPM. In this study using basic research, aims to provide input to existing theories, so that the Cattari Ariya Saccani based MSS conceptual model can balance MSS that are material, rational, and related to formal mechanisms.